Exploring the link between managerial outcomes and investment performance of entrepreneurs - Arranz Garcia, Juan David; Vicente Lorente, Jose David (Serbian Journal of Management, 2014)
This work represents a first attempt to explore possible interactions between the decisions of real and financial investment of an agent that behaves simultaneously as an entrepreneur and as an investor in the stock market. Specifically, we propose a set of hypotheses about the relationship between risk and investment results in real assets, and similar indicators relating to their assets portfolio in capital markets. Taking the “entrepreneur-investor” as the unit of analysis in the Spanish context, we test several hypotheses related to the relationship between indicators of profitability and business growth, and measures of return of investment companies with variable capital (i.e. “Sociedades de Inversión de Capital Variable”; SICAVs) which are significantly owned by the entrepreneur/investor. From a sample that includes 69 significant owners of both real investments and SICAVs during the period 2006-2010, our results confirm that there is a significant and positive relationship between the profitability of both the entrepreneur’s real business and her SICAV. We also found a negative link between the growth of the real business and profitability of the SICAV is also detected. Finally, the implications of these findings are presented and discussed.